Antimalarial activity, toxicity and phytochemical screening of quercus infectoria gall crude extracts - Zin, Nik Nor Imam Nik Mat (2021)
The reduced efficacy of the mainstay antimalarial drugs due to widespread of drug-resistant Plasmodium falciparum has necessitated efforts to discover new antimalarial drugs with new targets. Quercus infectoria galls have been used traditionally as a herbal remedy for post-partum medication and treatment of parasitic diseases. However, the antimalarial activity of the galls has not been reported. Thus, this study was aimed at evaluating the in vitro antimalarial activity of Q. infectoria gall crude extracts. This study was also designed to evaluate the toxicity profiles and screen the phytochemical constituents. The antimalarial potential of acetone, methanol, ethanol and aqueous extracts against the chloroquine-sensitive strain (3D7) of P. falciparum was assessed via malarial SYBR Green-I fluorescence-based (MSF) assay. Only acetone and methanol extracts showed a promising antimalarial activity with 50% inhibitory concentration (IC50) of 5.86 (1.64) and 10.31 (1.90) μg/mL, respectively. The cytotoxicity of the extracts was evaluated against mouse fibroblast cell (NIH/3T3), monkey kidney epithelial cell (Vero) and primary human umbilical vein endothelial cell (HUVEC) via 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay. The acetone and methanol extracts showed 50% cytotoxicity concentration (CC50) ranged from moderate toxic to non-toxic against all tested normal cells. The cytotoxicity evaluation using a brine shrimp lethality test (BSLT) showed that all extracts were non-toxic according to Meyer’s toxicity index. In addition to the haemolytic assay, a 2,2-diphenyl-1-picrylhydrazyl (DPPH)-based antioxidant assay of the extracts was performed to observe its connection with haemolysis of human erythrocytes (A+, B+, AB+ and O+ blood groups). No haemolytic effect was observed on the erythrocytes treated with all extracts. All extracts exhibited excellent DPPH radical scavenging activities. The concentration of heavy metals (lead, zinc, chromium, copper and cadmium) analysed with atomic absorption spectroscopy (AAS) in all extracts was below the permissible level according to WHO guidelines. The phytochemical screening revealed the presence of tannins and flavonoids, and high amount of total phenolic content (TPC) and total flavonoid content (TFC) in all extracts. The effect of acetone extract which previously exhibited the most promising antimalarial activity and have satisfactory selectivity index (SI) values on the pH of the parasite’s digestive vacuole was examined using a ratiometric fluorescent probe, fluorescein isothiocyanate (FITC)-dextran incorporated into mid trophozoite stage-infected erythrocytes and analysed by flow cytometry. The pH of the digestive vacuole of acetone extract-treated parasites was significantly altered in a concentration-dependent manner compared to the untreated parasites (p < 0.001). Overall, this study provides valuable insights of Q. infectoria gall capability as a safer and promising antimalarial candidate.